Adsensory financialisation - Odih, Pamela (Cambridge Scholars Publishing, 2016)
Adsensory technology presupposes a neoliberal entrepreneurial self as an integral feature of its biopolitical financialisation of healthcare regimes. According to Michel Foucault, neoliberalism is indebted to the endeavour of its self-disciplined subjects, investing human capital in a self-regulated, entrepreneurial pursuit of responsible healthcare and well-being. Primarily informed by social network analytics and virtual ethnographic observations, this book identifies the biopolitical basis of adsensory technologies. It argues that a paradoxical feature of adsensory technologies dissimulatin.